On the syntactic composition of manner and motion - Zubizarreta, Maria Luisa (Linguistic inquiry monographs, 2007)
Unlike many books and articles that discuss the relation between constructional meaning and the lexicon, 'On the Syntactice Composition of Manner and Motion' examines one phenomenon in detail: the articulation of manner and motion, in three distinct language families - Germanic, Korean, and Romance.